PENGARUH PEMBIAYAAN BANK UMUM SYARIAH TERHADAP PERKEMBANGAN USAHA MIKRO, KECIL, MENENGAH DI INDONESIA (Pendekatan Vector Error Correction Model) - Noviana, Delia Risma (Universitas Nusantara PGRI Kediri, 2022)
This study aims to analyze the long-term influence of Islamic banking financing on the development of MSMEs in Indionesia and to analyze the casual relationship between Islamic banking and the development of MSMEs in Indonesia. The data used in this study are secondary time series data form 2003-2020. The analysis method used is the Vector Error Correction Model (VECM) with the help of STATA 16. The results show that Islamic commercial bank financing on the development of MSMEs in Indonesia in the long term and short term have an effect that can be seen in the VECM test (long term and short term). P-value < tolerance level, that is long term 0.006 , 0.05 and short term 0.000 < 0.05. The financing variable for Islamic commercial banks affects MSMEs can be seen in the granger causality test shows F. Statistic > F. Table, where the financing variabke for MSME development is 0.000 < 0.05 while the MSME development variable affects Islamic commercial bank financing 0.042 < 0.05.